2009
DOI: 10.2139/ssrn.1342557
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure Decisions in Family Firms - Empirical Evidence from a Bank-Based Economy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
69
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 2 publications
10
69
2
1
Order By: Relevance
“…These results are statistically significant. Another study confirming the lower leverage ratios is conducted by Ampengerger et. al (2009) who explore the situation of German family firms.…”
Section: Empirical Studies Of Family Ownership and Capital Structurementioning
confidence: 61%
“…These results are statistically significant. Another study confirming the lower leverage ratios is conducted by Ampengerger et. al (2009) who explore the situation of German family firms.…”
Section: Empirical Studies Of Family Ownership and Capital Structurementioning
confidence: 61%
“…Analysing the papers composing our review, we notice that the adoption of relationship lending could be subject to differences in the institutional setting among countries. In countries like Continental Europe, stock markets are underdeveloped compared to Anglo-Saxon economies, firms rely heavily on bank lending and the firm ownership structure is heavily concentrated (La Porta et al, 1998;Ampenberger et al, 2013). Based on this distinction, it seems that relationship lending should be preferred in bank-based economies.…”
Section: Differences Between Financial Systemsmentioning
confidence: 99%
“…Another important difference that might be worth looking at is whether the fact that the family firm is located in a bank-based or market-based economy might influence a family firm's financial decisions. Studies that focused on capital structure decisions of family firms in a bank-based economy showed that the level of leverage is the lowest if the founding family is both a large shareholder and present in the management board at the same time, which is similar to studies in market-based economies (Ampenberger, Schmid, Achleitner, and Kaserer 2013). Whether the location of a family firm in a bank-based or market-based economy would affect its use of external equity remains to be seen.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 57%